2015
DOI: 10.1002/admi.201400444
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Wetting in the Hydrophobic Wenzel Regime

Abstract: wetting property on desired surfaces. [1][2][3] In addition, it was also found that unidirectional wetting can also be achieved on a surface through the deposition of a coating with a surface energy gradient, [ 10 ] or by decorating it with an orderly array of Janus nanostructures, which possess a hydrophilic face on one side and a hydrophobic face on the other. [ 5,11,12 ] When a water droplet is deposited on these nanostructures and if the substrate material is suffi ciently hydrophilic ( α < 65°, where α re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(56 reference statements)
0
9
1
Order By: Relevance
“…Interestingly, we find that the allowed line motion is not with the cones, as intuition suggests, but against the cones. This result also contrasts with most previous studies with tilted surface features [14][15][16][17]20 where easy motion is found along the feature direction. Motion against the features has only been observed on sharp tilted cones, a system very similar to ours 19 and asymmetric high aspect ratio polymeric posts 24 .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we find that the allowed line motion is not with the cones, as intuition suggests, but against the cones. This result also contrasts with most previous studies with tilted surface features [14][15][16][17]20 where easy motion is found along the feature direction. Motion against the features has only been observed on sharp tilted cones, a system very similar to ours 19 and asymmetric high aspect ratio polymeric posts 24 .…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, this data point has not been included in the following analysis. We first compare these experimental results to a simple line average model 16,19,26 . Following the rule of mixture, we average wetting conditions along the triple line 21,22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Surface energy patterns combined with pillar topographies can also be utilized for creating anisotropic wetting, as demonstrated by uni-bi-, and -tridirectional wetting based on oblique glancing angle deposition. 20,21 Anisotropic wetting can also be achieved based strictly on surface energy patterns without a topographic contribution, as demonstrated by bidirectional wetting on top of hydrophilic grooves. 22 Temperature tunable unidirectional wetting has been achieved through a poly-(N-isopropylacrylamide) coating on top of the prism structure 23 or a half shell nanocone structure.…”
Section: Introductionmentioning
confidence: 99%